(untitled) - FAO (Rome, Italy, 1995)
This book is compilation of statistics on nominal catches of fish, crustaceans, molluscs and other aquatic animals, residues and plants. The statistics are presented by country or territory, species, major fishing area and year, and for various aggregations
Keywords: fisheries - catch effort,fisheries - fishing effort,fisheries - statistics